The seasonal migratory behavior of sympatric anadromous Arctic charr and brown trout - Jensen, Jenny Lovisa Alexandra (2013)
The papers of this thesis are not available in Munin: 1. Jensen, J. L. A. & Rikardsen, A. H.: 'Do northern riverine anadromous Arctic charr Salvelinus alpinus and brown trout Salmo trutta overwinter in estuarine and marine waters?', Journal of Fish Biology (2008), vol. 73(7):1810-1818, available at http://dx.doi.org/10.1111/j.1095-8649.2008.02042.x 2. Jensen, J. L. A. & Rikardsen, A. H.: 'Archival tags reveal that Arctic charr Salvelinus alpinus and brown trout Salmo trutta can use estuarine and marine waters during winter', Journal of Fish Biology (2012), vol. 81(2):735-749, available at http://dx.doi.org/10.1111/j.1095-8649.2012.03343.x 3. Jensen, J. L. A., Rikardsen, A. H. & Davidsen, J. G.: 'Seasonal migrations and marine area use of sympatric Arctic charr Salvelinus alpinus and brown trout Salmo trutta from rivers without access to lakes' (manuscript) 4. Jensen, J. L. A., Rikardsen, A. H., Thorstad, E. B., Suhr, A. H., Davidsen, J. G. & Primicerio, R.: 'Fjord temperatures shape the marine area use of Arctic charr Salvelinus alpinus and brown trout Salmo trutta' (manuscript) This thesis used acoustic and archival telemetry to study fish migrations within and between freshwater and marine habitats. The main novel finding from this thesis work is that both Arctic charr and brown trout originating from rivers without access to lakes can be found in marine waters also during winter. The physical properties of the freshwater habitat may be the main factor controlling in which habitat fish reside during the winter. The fish that left the river during winter were mainly recorded in the estuary, but also in the sea up to 20 km away from the river outlet. There was large individual variation in migratory behavior, and individual fish were documented to reside in pure marine waters for periods lasting from a few hours to several months. The summer migratory behavior study of Arctic charr and brown trout showed that the species segregated in horizontal area use, where Arctic charr preferred colder ...